Ön ödemeli konut satış sözleşmesi - Çelikel, Ali Yaşar (My University, 2022)
Ön ödemeli konut satış sözleşmeleri ülkemizde inşaat sektörünün hız kazanmasıyla birlikte çok sık rastlanılan sözleşme tiplerinden biridir. Bu sözleşmenin bünyesinde tüketici için ciddi riskler barındırması sebebiyle 6502 sayılı Tüketicinin Korunması Hakkında Kanun ile düzenlenmiştir. İlgili yasa ve sonrasında çıkarılan yönetmelik ile tüketiciyi koruma amacıyla çeşitli düzenlemeler getirilmiştir. Sözleşmenin şekli, zorunlu içeriği, tüketicinin cayma ve dönme hakları hem yasada hem de yönetmelik hükümleri ile düzenlenmiştir. Bu çalışmada, ön ödemeli konut satış sözleşmeleri konusu, unsurları, tarafların hak ve yükümlülükleri bağlamında incelenecek ve uygulamada karşılaşılan sorunlar değerlendirilerek yargı kararları eleştirel bir analize tabi tutulacaktır.

Prepaid housing sales contracts became one of the most common types of contracts with the acceleration of the construction sector in Turkey. Since this contract contains serious risks for the consumer, it has been regulated by the Law No. 6502 on the Protection of the Consumer. Various regulations have been created in order to protect the consumer with the related law and the regulation issued after it. The form of the contract, its mandatory content, the consumer's right of withdrawal and consumers right of rescission are regulated both in the law and by the provisions of the regulation. In this study, the subject and elements of prepaid housing sales contracts will be examined in the context of the rights and obligations of the parties; and judicial decisions will be critically analyzed by evaluating the problems encountered in practice.
Keywords: Civil law; consumer; consumer contracts; House selling; Konut satışı; Medeni hukuk; Ön ödemeli konut satış sözleşmesi; tüketici; tüketici sözleşmeleri Prepaid housing sales contracts